"Night With Ike" dinner at Case Institute of Technology - Dow Chemical Company; Rebman Photo Service (1961)
Group photograph depicting "Night with Ike" dinner held at Case Institute of Technology in Cleveland, Ohio. Dwight D. Eisenhower, who served as the 34th President of the United States from 1953 to 1961, is positioned at the center of the photograph shaking hands with Case President T. Keith Glennan. Per correspondence accompanying the photograph, the other individuals depicted in the photograph are identified as follows (left to right): Charles M. White (retired chairman of the board, Republic Steel Corporation); Frederick C. Crawford (Trustee Chairman); and Dr. Charles J. Strosacker (Dow Chemical Company).
Keywords: Dow Chemical Company; Corporations; Chemical industry; Presidents; Eisenhower, Dwight D. (Dwight David), 1890-1969; White, Charles M.; Crawford, Frederick C., 1891-1994; Glennan, Thomas Keith, 1905-1995